Community-based model for management and follow-up by non-physician healthcare workers to improve awareness, treatment, and control of hypertension: The COTRACO study protocolDetailed key messages: - A.J. Lora Mantilla; L.A. Parra Gomez; P.A. Camacho-López; J. Otero-Wandurraga; B. Novella; A. González-Medina; O. Valdez-Tiburcio; F. Lanas; M.C. Rocha-Lezama; J. Alonzo-Arias; C. Rivilla-Piñango; C. Cáceres-Ramírez; et al. (Heliyon)
Introduction: Cardiovascular diseases are the leading cause of death and morbidity worldwide, with a significantly higher burden in low- and middle-income countries. Hypertension, a major risk factor for cardiovascular morbidity and mortality, remains under-diagnosed and poorly controlled, especially in regions such as Latin America. The HOPE-4 study demonstrated that the involvement of non-physician health workers (NPHWs), the use of standardized treatment algorithms, the provision of free antihypertensive drugs and home follow-up can significantly improve hypertension control and reduce cardiovascular risk, as demonstrated in Colombia and Malaysia. On this basis, the COTRACO study aims to address the barriers to hypertension treatment in low- and middle-income countries by implementing a similar standardized treatment approach delivered by non-specialist health workers. Methodology: The COTRACO study is a quasi-experimental, parallel-group, non-randomized, before-and-after study. A community-based model will be implemented in 600 patients in Colombia and the Dominican Republic, involving NPHWs to: 1) apply standardized treatment algorithms, 2) promote adherence to healthy lifestyles, and 3) provide standardized pharmacological treatment. Propensity Score Matching will be used to select 300 patients in Chile and 1200 in Spain for comparison with standard care in these populations. Expected outcomes: The primary outcome at 12 months of follow-up is the percentage of patients achieving controlled hypertension (defined as systolic BP < 140 mmHg and diastolic BP < 90 mmHg, or < 130 mmHg, and diastolic BP < 80 mmHg for diabetic patients), ensuring it is not inferior to that achieved in the control countries. Secondary outcomes include changes in BP levels, cholesterol levels, BMI, handgrip strength, waist-to-hip ratio, smoking status, Interheart risk score, diet, and physical activity at 6 and 12 months. Recommendations: If this model demonstrates superior outcomes compared to usual care, it is recommended that health authorities in low- and middle-income regions adopt and implement this approach. Using non-medical health professionals, standardized treatment algorithms and free access to antihypertensive medications, these regions can significantly improve awareness, diagnosis and management of hypertension. This strategy has the potential to reduce cardiovascular morbidity and mortality, thereby improving overall public health outcomes.